Resurfacing Severe Facial Burn Scars: An Algorithm Based on Three Different Types of Prefabricated Expanded Flaps - Xie, Feng; Zhu, Hainan; Gu, Bin; Zan, Tao; Liu, Kai; Li, Qingfeng (Journal of Reconstructive Microsurgery, 2014)
Background In the reconstruction of facial burn scars, large, thin, color-matching flaps are desirable due to aesthetic and functional demands. There have been many reports using prefabricated flaps to resurface facial skin lesions. However, an algorithm to select the most suitable treatment option for the individual patient is lacking.Methods An algorithm for facial resurfacing based on three types of prefabricated flaps from the cervical, periclavicular, and lateral thoracic area was setup, and 15 were patients treated accordingly.Results All 15 prefabricated flaps survived. Minor necrosis at the distal flap edge developed in three cases. After a follow-up of at least 6 months, all patients showed satisfactory aesthetic and functional outcomes.Conclusion By individual selection of the most suitable option among these three types of prefabricated flaps, satisfactory resurfacing can be achieved for most facial burn scars.
Keywords: prefabricated flap; expanded flap; temporal superficial vessel; lateral femoral circumflex vessel